Hubungan Peran Guru Terhadap Perilaku Disiplin Siswa Kelas IV SDN 005 Kempas Jaya Kabupaten Indragiri Hilir - Andini, Cicih; Ain, Siti Quratul (Cetta: Jurnal Ilmu Pendidikan, 2025)
Student disciplinary behavior is a crucial component in supporting the success of the learning process at school. Students with a high level of discipline tend to be more focused, responsible, and respectful of applicable rules. In this context, teachers play a strategic role in instilling discipline values through guidance, role modeling, and consistent as well as continuous supervision. This study aims to determine the relationship between the teacher's role and the disciplinary behavior of fourth-grade students at SDN 005 Kempas Jaya, Kempas District. The method used was a quantitative approach with a survey technique. The data collection instrument was a questionnaire that had undergone validity and reliability testing to ensure the appropriateness and accuracy of the data collected from respondents. The results showed that out of 15 statement items in the questionnaire, 12 were declared valid based on the Product Moment correlation test using SPSS version 22. The reliability test using Cronbach’s Alpha yielded a score of 0.900 for the teacher’s role variable and 0.732 for the student disciplinary behavior variable. Both values exceed the minimum threshold of 0.60, indicating that the instrument is reliable and suitable for use in this study. The normality test showed that the data were normally distributed (Sig. > 0.05), the homogeneity test showed homogeneous data variance (Sig. > 0.05), and the linearity test indicated a linear relationship between variables (Sig. = 0.007 < 0.05). The t-test result showed that tcount = 2.947 > ttable = 2.048 with a significance value of 0.000 < 0.05. This indicates a significant relationship between the teacher’s role and students’ disciplinary behavior. In conclusion, the more optimal the teacher’s role in guiding, directing, and enforcing discipline, the higher the quality of student discipline behavior in the elementary school environment.